2022
DOI: 10.1155/2022/3325686
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of LINC01857 Increases Sensitivity of Gastric Carcinoma Cells to Cisplatin

Abstract: Background. The critical roles of long noncoding RNAs (lncRNAs) in the carcinogenesis and progression of cancers have been well documented. It was reported that lncRNAs were involved in chemotherapy resistance in various cancers. This study was aimed at clarifying the role of LINC01857 in cisplatin (DDP) resistance in gastric carcinoma (GC). Methods. The Cancer Genome Atlas (TCGA) database was used to analyze the expression of LINC01857 in GC tissues and normal tissues. The expression of LINC01857 in GC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We measured the viability of DDP-resistant GC cells under the impact of different DDP concentrations using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT; Sigma-Aldrich) with a view to confirming and visualizing the semi-inhibitory concentration (IC50) value of DDP. The IC50 value was defined as the concentration of DDP corresponding to 50% of cell viability inhibition rates in the curve [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…We measured the viability of DDP-resistant GC cells under the impact of different DDP concentrations using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT; Sigma-Aldrich) with a view to confirming and visualizing the semi-inhibitory concentration (IC50) value of DDP. The IC50 value was defined as the concentration of DDP corresponding to 50% of cell viability inhibition rates in the curve [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%